(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
In this article, we’ll be looking to see if any landscape has an ambience. In doing so, we first highlight what in the landscape is opposed to ambience, namely detachment and distance, and then indicate that it is thanks to this detachment that the viewer’s participation in the landscape is possible as ambience. In this way, we attempt to show that any landscape, taken in an narrow aesthetic sense, implies a complementary double operation of withdrawal and fusion, contemplation and atmosphere, but that it cannot be totally identified with an atmosphere, however holistic it may be.